Yield structure components of autumn- and spring-sown pea (Pisum sativum L.) - Reinhard W. Neugschwandtner; Alexander Bernhuber; Stefan Kammlander; Helmut Wagentristl; Agnieszka Klimek-Kopyra; Hans-Peter Kaul (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2020)
Climate change brings increasing attention to winter sowing of traditionally spring sown crops. Crop stand height, soil coverage, grain yield and yield components of six winter pea varieties and one spring pea variety were compared in eastern Austrian growing conditions in 2014 and 2015. Crop stands of winter pea were taller up to the end of May before they declined and crop stands of spring pea were taller from early June on. Winter pea covered the soil at least partly over winter and showed faster soil coverage in spring. At the end of May, just some weeks before harvest, spring pea attained equal soil coverage. Grain yield of winter pea was almost double that of spring pea due to higher pod density whereas spring pea produced more grains pod−1 than four out of six winter pea varieties and a higher thousand grain weight than all winter pea varieties. Consequently, grain density was higher for winter pea while the single pod yield was higher for spring pea. Growing winter peas in Central Europe might be a good strategy for increasing grain legume productivity and thereby European feed protein production.